STUDY OF OXYTOCIN INJECTION EFFECT ON SOME SEMEN TRAITS AND LIBIDO IN TURKISH AND LOCAL AWASSI RAMS - Falah AL-Hassan; Muhammad N. Abdullah; NaderY. Abbo; Ghassan I. Abdullah (Mesopotamia Journal of Agriculture)
ر This study was conducted at AL-Rashidia animal breeding station / Nenava researches department. 20 rams (10 Turkish Awassi and 10 local Awassi rams) were used, every genetic group divided into two groups: The first group (5 rams) are injected with 0.5 ml. normal saline (control group) and the second group (5 rams) were injected with 0.5 ml. oxytocin (10 IU/ml.). The results showed that there was no significant effect for genotype on all semen traits in Turkish and local Awassi rams, on the other hand the treated group was significantly better than control group in all semen traits except individual motility and abnormal sperm. There was no significant differences between the two genotypes in libido traits. The treated group was significantly better than control group in the time and number of jumps for first mating only. There was no significant effect for interaction in all studied traits except the Turkish rams in number of jumps without breeding for Turkish rams as compard with control and treated group.